Flebotomíneos em peridomicílios rurais: como fatores ambientais, animais e limpeza do peridomicílio influenciam na abundancia desses dipteros - BRITO, Gustavo Almeida (2017)
The spread of leishamniasis is a worldwide problem that affects more than 80 countries. One way to combat the disease is by controlling the vector (Phlebotomine). To understand how the abundance of this diptera is influenced by environmental variables, by the cleanness of the peridomicile and by domestic animals around the rural residences. There were collected samples in 112 rural peridomiciles with a CDC trap in cities that are part of the Lençóis Maranhenses National Park. As a result, 3169 phlebotomines were captured and they were from 11 species. The variables that increased the abundance of phlebotomines were: animals presence, bodies of water proximity, and low vegetation cover. The cleaning of the peridomicile contributed to the abundance of males phlebotomines. Besides, three animals contributed to the inducement of these diptera to the peridomicile: chickens, horses and pigs.